New approaches to natural anticancer drugs - Saeidnia, Soodabeh (SpringerBriefs in Pharmaceutical Science & Drug Development, 2015)
This book provides an up-to-date review of recently identified natural anti-tumor compounds from various natural origins including plants, fungi, endophytic fungi and marine organisms. It also includes discussion of new areas such as biotechnology and nanoparticles. Chapters explain the challenges and developments in anti-cancer drug discovery approaches, traditional remedies for prevention and treatment of cancer, marine-derived anti-cancer compounds, and antibiotics used as anti-cancer agents, as well as different classes of terpenoids and carbohydrates, which have been the subject of discussion in this field as efficient anti-cancer candidates. This book will be a concise guide for researchers in the field of pharmaceutical sciences, students and residents in pharmacy and medicine as well as those researching phytochemistry and natural products.